Sodium yttrium fluoride based upconversion nano phosphors for biosensing. (May 2015) - Nampi, Padmaja Parameswaran; Varma, Harikrishna; Biju, P R; Kakkar, Tarun; Jose, Gin; Saha, Sikha; Millner, Paul
Abstract: In the present study, NaYF4 -Yb 3+ /Er 3+ having the composition NaYF4 -18%Yb 3+ /2%Er 3+ and NaYF4 -20%Yb 3+ /2%Er 3+ with and without the addition of PVP (polyvinyl pyrolidone) have been synthesised by a solution method using NaF, yttrium nitrate, ytterbium nitrate and erbium nitrate as precursors. Upconversion spectra of prepared nanomaterial under 980 nm laser excitation have been studied. The variation in upconversion spectra with new born calf serum and myoglobin has been studied. Myoglobin (Mb) may be helpful when used in conjunction with other cardiac markers for rapid determination of acute myocardial ischemia, especially in patients with a typical chest pain or nonspecific ECG changes. The variation of UC fluorescence with addition of Mb indicates the suitability of using NaYF4 based UC nanoparticles in cardiac marker detection. The detailed study is currently under progress.